De l’espoir pour la Jamaïque - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
De l’espoir pour la JamaïqueEn août 1999, Phyllis March, une agricultrice jamaïcaine, n’arrivait plus